“有的投票人(T(x))赞成(Z(x,y))所有的侯选人(H(y))”的谓词公式是
举一反三
- “有的投票人(T(x))赞成(Z(x,y))所有的侯选人(H(y))”的谓词公式是 A: x(T(x)∧y(H(y)→﹁Z(x,y)) B: x(T(x)∧y(H(y)→Z(x,y)) C: x(T(x)∧y(H(y)→Z(x,y)) D: x(T(x)∧y(H(y)∧Z(x,y))
- 公式"x ( F(x,y,z ) → "y ( G(x,y,z) → "z H(x,y,z) ) )的前束范式为 A: "x$y$z (F(x,t,w) → ( G(x,y,w ) → H(x,y,z) ) ) B: $x$y$z (F(x,t,w) → ( G(x,y,w ) → H(x,y,z) ) ) C: "x"y$z (F(x,t,w) → ( G(x,y,w ) → H(x,y,z) ) ) D: "x$y"z (F(x,t,w) → ( G(x,y,w ) → H(x,y,z) ) )
- 谓词公式"xP(x,y)Ù$t(Q(t,z)→"x$yR(x,y,t))中量词$t的辖域是() A: $t(Q(t,z)→"x$yR(x,y,t)) B: Q(t,z)→"x$yR(x,y,t) C: "x$yR(x,y,t) D: Q(t,z)
- 在谓词公式("x)(F(x)ÞG(y))Þ($y)(H(x)∧L(x, y, z))中,($y)的辖域是( ) A: F(x) B: ("x)(F(x) C: (H(x)∧L(x, y, z)) D: (F(x)ÞG(y))
- 中国大学MOOC: 在谓词公式(x)(F(x)ÞG(y))Þ($y)(H(x)∧L(x, y, z))中,(x)的辖域是( )